Desain Evaluasi Pembelajaran Pendidikan Agama Islam - Azman, Wan; Harahap, Nasrun (Indonesian Journal on Education (IJoEd), 2025)
In response to contemporary educational advancements, the purpose of this study is to investigate andconstruct an efficient, all-encompassing, and flexible framework for evaluating Islamic ReligiousEducation (PAI). Library research is the method employed, which involves examining a variety ofliterature sources, including books, scholarly journals, and pertinent documents. To obtain a thoroughgrasp of PAI learning evaluation, the analytical method entails a review of the literature that looks atideas, theories, and earlier research findings. According to the study's findings, a comprehensive andgenuine method should be used to evaluate PAI learning, taking into account cognitive, emotional, andpsychomotor components. The three primary phases of this evaluation are follow-up, implementation,and planning. It has been demonstrated that incorporating more interactive techniques with technologybasedassessment improves student motivation for learning and the overall efficacy of training.Additionally, a methodical assessment helps Islamic educational institutions create better learningstrategies and raise educational standards.